Risk factors associated with hand tractor related injuries among rice farmers in Thailand - Chaiyanun Tangtong (2022)
Hand tractors are important machines used in the soil preparation process before sowing rice in the paddy’s of Thailand. Previous research on injuries in rice farming indicated that working with a hand tractor may be one of main causes of injuries. This study investigated the prevalence of hand tractor-related injuries, their association risk factors and characteristic of injuries. The data were collected by face-to-face interview to 377 farmers from nearly all districts in Phra Nakhon Si Ayutthaya province. Among these rice farmers, the prevalence of injury was 41%. The most common type of injury was cuts (43.9%) and the most common source of injuries was stepping on a golden apple snail shell (33.1%). The bivariate Poisson regression models showed that self-reported normal working conditions that were associated with the risk of injury included sleeping problems (RR = 1.39), “Hustle Work (working quickly to complete plowing)” (RR = 1.48), feeling fatigue before work (RR = 1.60), and normal use of a leveler as attached plow equipment (RR = 1.41). However, a multivariate model showed only normal use of a leveler as attached equipment was associated with an increased use of injuries (RR = 1.47) after controlling for the other factors that were significant in the bivariate models. These results suggest that job stress protection should be recommended or redesign of the leveler attachment developed for hand tractors used in rice paddy fields.